1996
DOI: 10.1099/0022-1317-77-2-309
|View full text |Cite
|
Sign up to set email alerts
|

An adenovirus recombinant expressing the spike glycoprotein of porcine respiratory coronavirus is immunogenic in swine

Abstract: The full-length spike (S) gene of porcine respiratory coronavirus (PRCV) was inserted into the genome of human adenovirus type 5 downstream of the early transcription region 3 promoter. The recombinant virus replicated in cultures of the swine testicle ST

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…The spike (S) glycoprotein of CoVs is known to be the major inducer of virus‐neutralizing antibodies responsible for protective antiviral immunity (Callebaut et al ., ; Torres et al ., ). Furthermore, the truncated version of the SARS‐CoV S protein (S1) has been shown to contain important antigenic domains (Babcock et al ., ).…”
Section: Advances In the Development Of Plant‐based Subunit Vaccinesmentioning
confidence: 98%
“…The spike (S) glycoprotein of CoVs is known to be the major inducer of virus‐neutralizing antibodies responsible for protective antiviral immunity (Callebaut et al ., ; Torres et al ., ). Furthermore, the truncated version of the SARS‐CoV S protein (S1) has been shown to contain important antigenic domains (Babcock et al ., ).…”
Section: Advances In the Development Of Plant‐based Subunit Vaccinesmentioning
confidence: 98%
“…Efforts to develop a vaccine against SARS are necessarily based on only the limited knowledge gained from studies of SARS-CoV, as well as on anti-CoV strategies that have been devised over the years. Several groups have shown that the spike glycoproteins are major inducers of neutralizing antibodies, providing protective immunity against many CoVs (7)(8)(9)(10)(11). Currently, the SARS-CoV S glycoprotein and its truncated versions are considered the best candidates for generation of a recombinant vaccine against this disease (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In this report, we investigated the potential of intranasal immunization with recombinant BAV-3 for inducing protective immune responses against BHV-1 challenge. While animal studies using recombinant human adenoviruses have been reported (Callebaut et al, 1996 ;Mittal et al, 1996 ;Prevec et al, 1989), the present study differs in two aspects. First, the experiment was done in calves, the natural host of BAV-3.…”
Section: Discussionmentioning
confidence: 44%
“…Although recombinant human adenoviruses have been shown to be effective vectors for the delivery of vaccine antigens to animals (Callebaut et al, 1996 ;Prevec et al, 1989 ;Torres et al, 1996), their use as a vaccine-delivery system in domestic animals is limited in part due to safety concerns. As non-human adenoviruses are species specific, the development of animal-specific adenovirus would be a logical choice.…”
Section: Discussionmentioning
confidence: 99%